Islamic Approaches in Multicultural and Interfaith Dialogue - M Aris Rofiqi; Mochamad Ziaul Haq (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2022)
Humans are created with diverse ethnic, religious, and cultural backgrounds. Thus, dialogue experience has become a part of the experiences in daily life. Dialogue expresses an important aspect of human beings, such as listening and responding sincerely to each other and building bonds between them. It emphasizes different perspectives, attitudes, and openness. Similarly, Interreligious dialogue refers to a positive relationship with reciprocity and cooperation among followers of different religions. This dialogue communicates thoughts and hearts between different faiths people to build a common goal. In building interfaith dialogue, several approaches can be applied where the participants can become open, accept and respect different truths. The purpose of dialogue in Islam is not to change one's beliefs but to open up space and opportunities for others to express their religious beliefs and practices. Islam teaches that every human being has the right to choose and practice his religion. Dialogue can be realized without having to change our faith, we can even hold on to our faith. This research applies qualitative methods through contextual analysis.